Uso de drogas, comportamentos no trânsito e saúde cardiometabólicas de caminhoneiros que trafegam pelas rodovias federais na região de Uberlândia – MG - Pereira, Nayline Martins (2020)
Objective: In view of the strenuous work routine of truck drivers, added to life habits adverse to health, this study aims to evaluate the health and work conditions, associated or not with drug use, of truck drivers who travel along federal highways in the region of Uberlândia - MG. Methodology: This is a descriptive, exploratory study with a quantitative approach. The sample consisted of truck drivers who travel on the federal highway network in the municipality of Uberlândia (MG), in the mesoregion of Triângulo Mineiro. The data were collected through reported author interviews, the Chi Square and Logistic Regression Tests were applied to obtain the results, adopting a significance level of 0.05 for all variables. Results: This study included 235 truck drivers, mostly male, with an average age of 42 years old, predominantly white, married, Catholic, sedentary, smokers, drinkers and wage earners, who work an average of 12 hours a day and cover an average distance of 1200 km / week. All the cardiovascular risk factors evaluated showed a statistically significant association with the truck drivers' job characteristics. Conclusion: It is concluded, then, that the professional truck drivers who travel on BR / 050 have risk factors for cardiovascular diseases. The history of robberies and traffic accidents, as well as the consumption of alcohol and tobacco are associated with cardiometabolic diseases, and it is imperative to recognize, through public health policies, work-related violence as a risk factor for cardiovascular disease outcomes and metabolic. Most of the cardiovascular risk factors identified in truck drivers are modifiable. Therefore, actions directed at this public demand greater attention from the health sector.